Ścieżki dywersyfikacji uprawiania gier sportowych jako wyznaczniki różnicowania kompetencji trenerów i team managerów – paradygmat a realia = Diversification of paths in sport games as a determinant of differentiating competences of trainers and team managers - the paradigm vs. reality - Panfil, Ryszard (Journal of Education, Health and Sport, 2016)
Panfil R. Ścieżki dywersyfikacji uprawiania gier sportowych jako wyznaczniki różnicowania kompetencji trenerów i team managerów - paradygmat a realia =Diversification of paths in sport games as a determinant of differentiating competences of trainers and team managers - the paradigm vs. reality. Journal of Education, Health and Sport. 2016;6(9):11-24. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.61622 http://www.ojs.ukw.edu.pl/index.php/johs/article/view/3830 https://pbn.nauka.gov.pl/sedno-webapp/works/746221 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 05.08.2016. Revised 25.08.2016. Accepted: 06.09.2016. Streszczenie Współczesne gry sportowe charakteryzuje nasilająca się dywersyfikacją ścieżek i faz ich rozwoju. Zróżnicowanie celów uprawiania gry na różnych ścieżkach wymaga jakościowego dostosowania do nich warunków ich osiągania, w tym tych wyznaczanych kompetencjami trenerów i organizatorów wspierających osoby uprawiające gry. Biorąc powyższe pod uwagę sformułowano cele publikacji, które objęły w kolejności: uzasadnienie potrzeby zdywersyfikowanego identyfikowania ścieżek i faz uprawiania gier sportowych, następnie zdefiniowano sieciowo - procesowy model pozwalający na elastyczną identyfikację ścieżek i faz rozwoju gier sportowych, uwzględniając dywersyfikację ścieżek i faz uprawiania gier sportowych ukazano nieadekwatności obecnie preferowanych w Polsce kompetencji trenerów i managerów i określono model jakościowo zróżnicowanych kompetencji w tym: trenera motoryki gracza, tutora adepta gry, coacha zespołu graczy i team managera. Słowa kluczowe: gry sportowe, ścieżki rozwoju, kompetencje trenerów i managerów Abstract Contemporary sport games are characterised by an increasing diversification of paths and phases one may select when determining one’s objective of engaging in a game. As these objectives - and, consequently, conditions of achieving them - change, trainers and other support personnel need to adapt their competences to one specific path and its accompanying objectives. In the light of the above, the purpose of this publication is to: justify the need for diversified identification of the above-mentioned paths and phases, subsequently, define a network-processual model that enables flexible identification of these paths and phases, explore the inadequacy of coaching and managing competences currently favoured in trainers and managers in Poland; finally, present a model of qualitatively diversified sets of competences, including: player’s fitness coach, talented player’s tutor, team coach and team manager. Keywords: sport games, development paths, competences of trainers and managers